24 hour hormone and serum electrolyte levels of dogs with pituitary-dependent hyperadrenocorticism treated with trilostane - Lehnert, Claudia; Justus Liebig University Giessen (My University, 2007)
Ten dogs with PDH took part in this study. After confirming the diagnosis, treatment with once daily trilostane was started. On their 10th and 30th day of therapy, the dogs were controlled clinically and an ACTH stimulation test was performed 3 to 4 hours after trilostane dosing. On the 30th day of therapy, the dogs were hospitalized and over 24 hours, blood samples were taken for the measurement of trilostane, ketotrilostane, endogenous ACTH, cortisol, aldosterone, renin and serum electrolytes. On the 10th and 30th day of therapy, clinical improvement was good in all but one dog. Laboratory findings including the ACTH stimulation test results had generally improved on the 30th day of therapy, although some of the parameters still were not within the reference range. None of the patients showed any adverse effects. Nevertheless, on the 30th day of therapy, one of the dogs collapsed suddenly and, although regenerating quickly, was removed from further blood sampling. Trilostane absorption was quick and ketotrilostane was formed immediately. For both substances, peak concentrations were reached 1.5 to 3 (4) hours after trilostane administration. Accordingly, lowest serum cortisol and aldosterone levels were found at nearly the same time points. Although cortisol and aldosterone levels were very low in all dogs, none showed any adverse effects. Because the negative feedback mechanism caused by high cortisol levels was removed, all dogs showed highest endogenous ACTH levels 4 to 8 hours after trilostane dosing. At all time points, all dogs had endogenous ACTH levels well above the reference range. Because there was quite marked inter-individual variation over the 24 hours and in some dogs changes in endogenous ACTH levels were only minimal, its measurement is most likely not useful for the evaluation of therapeutical success of trilostane. Serum renin activity remained rather unchanged during the day. While changes in serum sodium and calcium were insignificant, serum potassium showed some astonishing development: At times when aldosterone was at its lowest concentration and high potassium levels would be expected, potassium levels were low, but nevertheless well inside the reference range. An aldosterone-like effect of trilostane or of accumulating steroid precursors seems possible, although further studies are necessary to verify these hypotheses. This may be one of the reasons why trilostane is more secure in the treatment of PDH than lysodren.

Zehn Hunde mit hypophysärem Hyperadrenokortizismus nahmen an dieser Studie teil. Nachdem die Diagnose gesichert wurde, begann die Therapie mit einmal täglich verabreichtem Trilostan. Die Hunde wurden am 10ten und 30ten Tag der Therapie sowohl klinisch als auch mittels ACTH-Stimulationstest (3 bis 4 Stunden nach der Gabe von Trilostan) kontrolliert. Am 30ten Tag der Therapie wurden die Tiere stationär aufgenommen und über 24 Stunden Blutproben genommen zur Bestimmung von Trilostan, Ketotrilostan, endogenem ACTH, Kortisol, Aldosteron, Renin und Serumelektrolyten. Am 10ten und 30ten Tag der Behandlung zeigten alle Hunde außer einem ein gutes klinisches Ansprechen auf die Therapie. Die Ergebnisse der Laboruntersuchungen inklusive der durchgeführten ACTH-Stimulationstests ergaben grundsätzlich bessere Werte, auch wenn nicht alle Resultate den Normbereich erreichten. Keiner der Patienten zeigte Nebenwirkungen. Dennoch kollabierte einer der Hunde plötzlich am 30ten Tag der Therapie, und obwohl er sich sehr schnell wieder regenerierte, wurde er aus der Studie entfernt. Die Absorption von Trilostan geschah schnell und Ketotrilostan wurde direkt gebildet. Höchste Konzentrationen beider Substanzen waren 1,5 bis 3 (4) Stunden nach der Gabe von Trilostan nachweisbar. Entsprechend wurden die niedrigsten Werte des Serumkortisols und des Serumaldosterons zum annähernd gleichen Zeitpunkt gefunden. Obwohl die Konzentrationen des Kortisol und des Aldosterons in allen Hunden sehr niedrig waren, zeigte keiner der Patienten Nebenwirkungen.Nach Wegfall des negativen Rückkopplungsmechanismus durch hohe Kortisolwerte zeigten alle Hunde höchste Werte des endogenen ACTH 4 bis 8 Stunden nach Tablettengabe. Zu allen Zeitpunkten hatten alle Hunde endogene ACTH-Werte weit über dem Normalbereich. Da sich eine starke Variation der Werte zwischen den Individuen während der 24 Stunden nachweisen ließ und einige Hunde nur minimale Veränderungen der Konzentration des endogenen ACTH zeigten, erscheint die Messung des endogenen ACTH nicht nützlich zur Überprüfung des Therapieerfolges von Trilostan. Die Serumreninaktivität blieb mehr oder weniger unverändert. Während sich auch die Konzentrationen der Serumelektrolyte Natrium und Kalzium nicht signifikant veränderten, wies Kalium eine erstaunliche Entwicklung auf: Zum Zeitpunkt der niedrigsten Aldosteronwerte, wenn entsprechend eher erhöhte Kaliumwerte zu erwarten wären, fanden sich niedrige Kaliumwerte, wenn auch noch innerhalb des Normalbereiches. Ein Aldosteron-artiger Effekt des Trilostans oder aber der sich bildenden Steroidvorläufersubstanzen wäre denkbar, auch wenn diese Hypothesen erst durch weitere Studien bewiesen werden müssen. Dies mag (unter anderem) die im Vergleich zum Lysodren bessere Verträglichkeit von Trilostan erklären.
Keywords: ddc:630